Integrative genomic analysis reveals DHX58 as a key player in gastric cancer - Yan Li; Liren Zhang; Zhi Wen; Haixia Wang; Kunming Zhang; Buzai Wang; Jinfan Li; Huiqing Kang; Yanjun Gao; Zhi Yu; Yongzhe Du (PLoS ONE, 2026)
Gastric cancer (GC) is a major global health burden with limited treatment options. Identifying the molecular mechanisms underlying GC progression is critical for developing novel therapeutic strategies. We integrated whole-genome bisulfite sequencing and bulk RNA sequencing to identify hub genes involved in GC. Functional annotations were performed using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses, supplemented by data from The Cancer Genome Atlas. Key findings were validated using western blotting, immunohistochemistry, quantitative real-time PCR, and methylation-specific PCR. DExH-box helicase 58 ( DHX58 ) was identified as a hypomethylated, highly expressed hub gene in GC. Mechanistically, DHX58 expression is regulated by the transcription factor CCAAT enhancer–binding protein α. Immune profiling further implicated DHX58 in the development of resistance to GC immunotherapy. Our study revealed that DHX58 hypomethylation drives its overexpression in GC, making it a promising therapeutic target. These findings offer new insights into the pathogenesis of GC and suggest potential immunotherapeutic approaches.